The Impact of Esg Performance on the Value of Family Firms: The Moderating Role of Financial Constraints and Agency Problems - Espinosa-Mendez, C (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
The main objective of this research is to shed more light on how ESG may be seen as a valuable investment for family firms. We study the impact of ESG performance on the value of family firms by considering the moderating role played by financial constraints and agency costs. Using an international sample of 254 firms that belong to the 500 largest family-owned firms worldwide over the period 2015–2021, we report that the overall ESG score is positively associated with firm value. Among the three ESG components, we find that environmental and social performances have a positive and statistically significant impact on firm value. However, we find no evidence of any significant effect of governance score on firm value. More importantly, we also find that the impact of ESG performance on firm value is lower under the presence of financial constraints and agency costs. © 2023 by the authors.